The whole book of Psalms / volume 2 - Sternhold, Thomas - (The whole book of Psalms collected into English metre by Thomas Sternhold, John Hopkins, and others : a critical edition of the texts and tunes, 2018)
The whole book of Psalms -- Historical essay -- Development and publication -- The Elizabethan Psalm book -- Later history of the Psalm book.